(untitled) (Ustozlar uchun, 2025)
This article examines the application of corpus linguistics in studying historical language change. It explores the role of diachronic corpora in tracking linguistic evolution in vocabulary, grammar, semantics, and syntax. The study emphasizes data-driven approaches, highlighting methods such as frequency analysis, collocation, semantic shift tracking, and concordance analysis. Additionally, it discusses various corpus tools used in historical research, along with their advantages and limitations. The findings illustrate how corpus-based methods contribute to a deeper understanding of language development over time.